Physical and Kinetic Evidence for an Association between Sucrose-Phosphate Synthase and Sucrose-Phosphate Phosphatase. - Echeverria, E. (1997)
The possible formation of a multienzyme complex between sucrose (Suc)-phosphate synthase (SPS) and Suc-phosphate phosphatase (SPP) was examined by measuring the rates of Suc-6-phosphate (Suc-6-P) synthesis and hydrolysis in mixing experiments with partially purified enzymes from spinach (Spinacia oleracea) and rice (Oryza sativa) leaves. The addition of SPP to SPS stimulated the rate of Suc-6-P synthesis. SPS inhibited the hydrolysis of exogenous Suc-6-P by SPP when added in the absence of its substrate (i.e. UDP-glucose) but stimulated SPP activity when the SPS substrates were present and used to generate Suc-6-P directly in the reaction. Results from isotope-dilution experiments suggest that Suc-6-P was channeled between SPS and SPP. A portion of the SPS activity comigrated with SPP during native polyacrylamide gel electrophoresis, providing physical evidence for an enzyme-enzyme interaction. Taken together, these results strongly suggest that SPS and SPP associate to form a multienzyme complex.